Association between serum resistin level and outcomes in kidney transplant recipients. (11th January 2016) - Nagy, Kristof; Ujszaszi, Akos; Czira, Maria E.; Remport, Adam; Kovesdy, Csaba P.; Mathe, Zoltan; Rhee, Connie M.; Mucsi, Istvan; Molnar, Miklos Z.
Summary: Resistin is an adipocytokine that is associated with inflammation, coronary artery disease, and other types of cardiovascular disease among patients with normal kidney function. However, little is known about the association of resistin with outcomes in kidney transplant recipients. We collected socio‐demographic and clinical parameters, medical and transplant history, and laboratory data from 988 prevalent kidney transplant recipients enrolled in the Malnutrition‐Inflammation in Transplant—Hungary Study (MINIT‐HU study). Serum resistin levels were measured at baseline. Associations between serum resistin level and death with a functioning graft over a 6‐year follow‐up period were examined in unadjusted and adjusted models. The mean±SD age of the study population was 51 ± 13 years, among whom 57% were men and 21% were diabetics. Median serum resistin concentrations were significantly higher in patients who died with a functioning graft as compared to those who did not die during the follow‐up period (median [IQR]: 22[15–26] vs. 19[14–22] ng/ml, respectively; P < 0.001). Higher serum resistin level was associated with higher mortality risk in both unadjusted and fully adjusted models: HRs (95% CI): 1.33(1.16–1.54) and 1.21(1.01–1.46), respectively. In prevalent kidney transplant recipients, serum resistin was an independent predictor of death with a functioning graft.